Applicability of the 60-minute balloon time: integrative review (Research, Society and Development, 2023)
Introduction: Cardiovascular diseases represent the main cause of mortality in the world. Proper management of Medical Myocardial Infarction is based on prompt clearance of the injured coronary artery through Coronary Transluminal Angioplasty, ensuring flow in the region, in addition to the reversal and monitoring of its possible arrhythmogenic complications. The European Society of Cardiology in 2018 defined that door-to-balloon time should be